2012
DOI: 10.1021/jp211429f
|View full text |Cite
|
Sign up to set email alerts
|

Phase, Morphology, and Hygroscopicity of Mixed Oleic Acid/Sodium Chloride/Water Aerosol Particles before and after Ozonolysis

Abstract: Aerosol optical tweezers are used to probe the phase, morphology, and hygroscopicity of single aerosol particles consisting of an inorganic component, sodium chloride, and a water insoluble organic component, oleic acid. Coagulation of oleic acid aerosol with an optically trapped aqueous sodium chloride droplet leads to formation of a phase-separated particle with two partially engulfed liquid phases. The dependence of the phase and morphology of the trapped particle with variation in relative humidity (RH) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 65 publications
2
82
0
Order By: Relevance
“…[62][63][64][65][66] Within the body of literature on O 3 reactions with aerosols, investigations of the ozonolysis of oleic acid aerosols are of particular interest because these particulates appear in relative high abundance in certain regions of the atmosphere. [67][68][69][70] From these studies, reactive uptake coefficients have been determined to be generally on the order of 10…”
Section: à7mentioning
confidence: 99%
“…[62][63][64][65][66] Within the body of literature on O 3 reactions with aerosols, investigations of the ozonolysis of oleic acid aerosols are of particular interest because these particulates appear in relative high abundance in certain regions of the atmosphere. [67][68][69][70] From these studies, reactive uptake coefficients have been determined to be generally on the order of 10…”
Section: à7mentioning
confidence: 99%
“…In adopting an equilibrium structure, the total surface free energy is minimized; if the change in surface areas is small then we can simply use the spreading coefficients to directly predict the morphology. This assumption was shown to hold for supermicron systems studied using the aerosol optical tweezers, for example, oleic acid added to aqueous NaCl produced a partially engulfed morphology (Kwamena et al 2010;Dennis-Smither et al 2012). Veghte et al (2013) has shown that phase separated supermicron particles can experience transitions to a homogeneous morphology as diameter decreases (d p < 196 nm for succinic acid with ammonium sulfate and d p < 270 nm for pimelic acid and ammonium sulfate).…”
Section: Introductionmentioning
confidence: 98%
“…In the cases where the phases are not expected or observed to mix the resulting phase-separation is usually assumed to adopt a core-shell morphology where one phase "coats" the other (Vaden et al 2011;Abramson et al 2013;Platt et al 2013;Robinson et al 2015). The occurrence of partial-shell morphologies and their importance for the timescales of physical and chemical evolution of aerosols has recently come to the fore requiring novel analytical techniques to fully assess their occurrence and impacts (Buajarern et al 2007a(Buajarern et al , 2007bKwamena et al 2010;Reid et al 2011;Dennis-Smither et al 2012;Shiraiwa et al 2012;Stewart et al 2015;Metcalf et al 2016). For a core-shell morphology, diffusion through the shell dictates the rate at which gas-phase components partition into similar aerosol components as the system re-equilibrates (Vaden et al 2011;Davies et al 2012;Abramson et al 2013;Lu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the considerable work that has been carried out in recent years, there is still much uncertainty about the fundamental properties of marine aerosol particles, such as chemical composition, mixing state, hygroscopicity, cloud droplet activation, formation, aging, and removal mechanisms (Gantt and Meskhidze, 2013;IPCC, 2013). Several laboratory studies about the effect of organic surfactants, such as palmitic and oleic acids, on NaCl, ammonium sulfate or mineral dust aerosol particles as a function of relative humidity have been reported employing a variety of experimental techniques, such as electrodynamic balance, infrared spectroscopy, electrical mobility, optical tweezers, cavity ring-down spectroscopy or nonlinear spectroscopy (Cwiertny et al, 2008;Davies et al, 2013;Dennis-Smither et al, 2012;Ebben et al, 2013;Garland et al, 2005;Hansson et al, 1998;Najera and Horn, 2009;Robinson et al, 2013;Rossi, 2003;Rubasinghege et al, 2013). The general conclusions are that hygroscopic growth, deliquescence relative humidity (DRH) and efflorescence of the particles at efflorescence relative humidity (ERH) may be affected by several factors, such as coating thickness or structural arrangement of the organic film.…”
Section: Introductionmentioning
confidence: 99%